Treasure hunt [compact disc, unabridged] - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery, 2013)
Inspector Montalbano is hailed as a hero after news cameras film him scaling a building, gun in hand, to capture a pair of unlikely snipers. Shortly thereafter the inspector begins to receive cryptic messages in verse from someone challenging him to a treasure hunt. Intrigued, he accepts, treating the messages as amusing riddles--until they take a dangerous turn.